Characterization of a Baculovirus-Encoded ATP-Dependent DNA Ligase - Pearson, Margot N. (American Society for Microbiology, 1998)
Sequence analysis of the Lymantria dispar multicapsid nucleopolyhedrovirus (LdMNPV) genome identified an open reading frame (ORF) encoding a 548-amino-acid (62-kDa) protein that showed 35% amino acid sequence identity with vaccinia virus ATP-dependent DNA ligase. Ligase homologs have not been reported from other baculoviruses. The ligase ORF was cloned and expressed as an N-terminal histidine-tagged fusion protein. Incubation of the purified protein with [α-(32)P]ATP resulted in formation of a covalent enzyme-adenylate intermediate which ran as a 62-kDa labeled band on a sodium dodecyl sulfate-polyacrylamide gel. Loss of the radiolabeled band occurred upon incubation of the intermediate with pyrophosphate, poly(dA) · poly(dT)(12–18), or poly(rA) · poly(dT)(12–18), characteristics of a DNA ligase II or III. The protein was able to ligate a double-stranded synthetic DNA substrate containing a single nick and inefficiently ligated a 1-nucleotide (nt) gap but did not ligate a 2-nt gap. It was able to ligate short, complementary overhangs but not blunt-ended double-stranded DNA. In a transient DNA replication assay employing six plasmids containing the LdMNPV homologs of the essential baculovirus replication genes, a plasmid containing the DNA ligase gene was neither essential nor stimulatory. All of these results are consistent with the activity of type III DNA ligases, which have been implicated in DNA repair and recombination.